The effectiveness of ABC method in small companies - Klimaitienė, Rūta; Rudžionienė, Kristina; Verbliugevičiūtė, Andželika (Buhalterinės apskaitos teorija ir praktika, 2014)
Under the current conditions of Economics, in order to keep competition it is necessary to possess not only good economical resources, but also to apply them relevantly in production and this is impossible without good administration in accounting of costs and productions costs. Before the calculation of product cost, first, it is necessary to know which costs and how many of them are included into the indicators of product cost. The validity and objectiveness of the obtained information depend on the preciseness of current cost distribution for the product cost. Scientific problem – it is unclear how ABC method affects the calculation of partial cost in small companies. It is not clear which method of cost calculation is most beneficial to apply for small companies –it is necessary to research how to distribute indirect costs – either applying ABC system (activity based costing - ABC) or using more simple – traditional distribution methods. The object is ABC method. The aim is to research the application efficiency of ABC method in small companies. In the first part there are analysed the pieces of research carried out by foreign authors investigating ABC method. There is executed the research in cost calculation in Lithuanian companies in order to identify if companies apply the following method, what benefit they receive and which difficulties they face. Having completed the analysis there were formulated advantages and disadvantages of the following method. In the second part, following the possessed cost calculation data of the company ‘Baldas’ there is compared the cost of the key company’s products calculated under traditional method and applying ABC method. It was indicated if it is useful for a company to apply ABC method for cost calculation.
Keywords: ABC method; small companies